The Contemporary world looking through the lenses of globalization - Bihasa, Carmelo Rico S. (Books Atbp. Publishing Corp., 2022)
"This book provides a unique and interesting introduction to the concept of globalization. It provides the students - who are engaged in the study of the contemporary world - with a sound and logical approach in analyzing and understanding the complex nature of globalization..."--Preface.